STUDI KELAYAKAN INVESTASI PERTAMBANGAN BATU GRANODIORIT DI DESA BASEH KECAMATAN KEDUNG BANTENG KAB. BANYUMAS - Suliyanto Suliyanto (Faculty of Economics and Business Universitas Jenderal Soedirman, 2007)
The aim of this research is to analyze the feasibility of granodiorit mining in Baseh, Kedung Banteng, Banyumas Regency. Several aspecst that analysed in this research are market aspect, technology aspect, production aspect, management aspect, and financial aspect. Market aspect, technology aspect, production aspect, management aspect, analysed by descriptive-comparative analysis while financial aspect is analyzed by investment criterion analysis: Payback Period (PP), Net Present Value (NPV), Index Profitability (PI), and Internal Rate of Return ( IRR). Based on the analyzis, it can be concluded that granodiorir mining in Baseh, Kedung Bandeng, Banyumas regency is feasible to be executed.